2010
DOI: 10.1002/pen.21687
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of polyethylene terephthalate/polyphenylene sulfide/barium titanate nanocomposite for application in electronic industry

Abstract: Polymer/ceramic nanocomposites designed for application as electronic packaging were prepared using corotating twin‐screw extruder. The dielectric properties of the composites made from polyethylene terephthalate (PET), polyphenylene sulfide, and barium titanate were studied as a function of BaTiO3 fraction in the range between 0.75 and 1.5 wt%. Processing parameters were optimized in order to obtain the nanocomposites with appropriate dielectric properties like dielectric permittivity ε′, dielectric losses ε″… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 40 publications
3
18
0
Order By: Relevance
“…2 (b), the loss modulus (E'') of the composites is seen to increase with the increase in fiber loading and to generate a relaxation transition peak at approximately 49.5 °C and 64.6 to 71.2 °C for neat rTPB and rTPB/RH composites, respectively. This peak could be attributed to the alpha (α)-relaxation transition of the resultant thermoplastic blends, which Yao et al (2011) reported for HDPE to be at 47 °C, while Konieczna et al (2010) reported for PET to be at 105 °C. It is established that α-relaxation is related to the complex multi-relaxation process, which is primarily related to the molecular mobility of the crystalline region of the polymer.…”
Section: Thermal Degradation and Stabilitymentioning
confidence: 91%
“…2 (b), the loss modulus (E'') of the composites is seen to increase with the increase in fiber loading and to generate a relaxation transition peak at approximately 49.5 °C and 64.6 to 71.2 °C for neat rTPB and rTPB/RH composites, respectively. This peak could be attributed to the alpha (α)-relaxation transition of the resultant thermoplastic blends, which Yao et al (2011) reported for HDPE to be at 47 °C, while Konieczna et al (2010) reported for PET to be at 105 °C. It is established that α-relaxation is related to the complex multi-relaxation process, which is primarily related to the molecular mobility of the crystalline region of the polymer.…”
Section: Thermal Degradation and Stabilitymentioning
confidence: 91%
“…In general, the most commonly used polymers are epoxy, polyethylene, polypropylene, polyethylene therephtalate, poly-methyl metacrylate, and poly-ethyletherketone, which meet the requirements for the low cost organic substrate process and mechanical flexibility, and can be upgraded with the advantages from the fillers/dopants and obtaining desirable dielectric properties. They find a variety of applications, especially in electronic systems, due to the growing demands of electronic miniaturization or packaging, increased functionality, high performance and low cost for novel material compositions with high dielectric constants [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. The dielectric properties of polymer compositions depend primarily on the content, size, and distribution of dopant particles as well as processing techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Literature values vary from 100-600 [48] (grain size < 0.7 m, much smaller than the dielectric constant of bulk BT ceramics), to ~2000 (for grain size of 10 m, for example), or ~5000 (for grain size between 0.7 and 1 m) [52]. The dielectric constant of these ceramic-polymer composites increases as the powder size decreases [37,[40][41][42]45].…”
Section: Introductionmentioning
confidence: 99%
“…In summary, the mechanical and thermal properties of high‐temperature thermoplastics exhibit a good potential for the development of insulating substrates for high‐frequency multilayer. However, quite surprisingly, only few investigations regarding the dielectric properties of these materials in the high‐frequency range (>10 MHz) can be found in the literature 32–36…”
Section: Introductionmentioning
confidence: 99%
“…However, quite surprisingly, only few investigations regarding the dielectric properties of these materials in the high-frequency range (>10 MHz) can be found in the literature. [32][33][34][35][36] To deeply analyze the potential of highly filled high-temperature thermoplastics for PCBs in high-frequency applications, the influence of three key factors (namely frequency, the filler fraction [talc, in this study], and the moisture absorption) on the dielectric behavior of PEI, PES, PEEK, and PPS are investigated in this article. A frequency range between 10 MHz and 1 GHz has been used for this investigation.…”
Section: Introductionmentioning
confidence: 99%